1991
DOI: 10.1210/endo-129-3-1175
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Gonadotropin-Releasing Hormone (GnRH) Secretion Leading up to Ovulation in the Ewe: Existence of a Preovulatory GnRH Surge*

Abstract: We have previously shown LH surges induced by physiological estradiol levels are invariably accompanied by robust and sustained GnRH surges in the ewe. Such an increase, however, has not been observed consistently during the preovulatory LH surge. In the present study, we examined GnRH secretion in Suffolk and Ile de France ewes during the preovulatory period using a method for pituitary portal blood collection which allows simultaneous portal and jugular blood samples to be taken at frequent intervals for up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
204
1
13

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(226 citation statements)
references
References 25 publications
8
204
1
13
Order By: Relevance
“…Studies of rats and sheep have indicated that a GnRH surge accompanies and is required for the LH surge (7)(8)(9)42), and more recent studies in rhesus monkeys have indicated that a GnRH surge is present and required in this species as well (10,43). In rodents, the amplitude of the GnRH surge has been reported to be too small to trigger a LH surge without an accompanying increase in pituitary responsiveness to GnRH (44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of rats and sheep have indicated that a GnRH surge accompanies and is required for the LH surge (7)(8)(9)42), and more recent studies in rhesus monkeys have indicated that a GnRH surge is present and required in this species as well (10,43). In rodents, the amplitude of the GnRH surge has been reported to be too small to trigger a LH surge without an accompanying increase in pituitary responsiveness to GnRH (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…This switch, in turn, leads to a large, continuous increase in GnRH levels in pituitary portal blood, or a GnRH surge, which serves as the final, prerequisite signal for the pituitary luteinizing hormone (LH) surge, subsequently initiating ovulation. Preovulatory GnRH surges have been demonstrated in rats (7), sheep (8,9), and monkeys (10).…”
mentioning
confidence: 99%
“…This may not only allow the mammalian GnRH-R to maintain signaling during sustained agonist exposure but may also prevent functional desensitization in circumstances where the receptors are repetitively challenged with agonist. These features may serve to maintain cellular sensitivity and responsiveness during events such as the GnRH surge that precedes the preovulatory luteinizing hormone surge (42) and allow the frequency encoded pattern of the hypothalamic pulsatile GnRH release (43) to be faithfully maintained at the level of the pituitary gonadotropes.…”
Section: Fig 4 Immunoprecipitation Studies On Chimeric Receptors (Rmentioning
confidence: 99%
“…It is well established from studies using sheep as a model (and in cattle to a lesser extent) that LH pulsatile secretion reflects the GnRH pulsatile secretion pattern (Moenter et al, 1991;Skinner et al, 1995;Skinner et al, 1997;Gazal et al, 1998). This has been tested and validated by the LH pulsatile infusion studies of Duffy et al (2000) in early postpartum anoestrous beef cows.…”
Section: Introductionmentioning
confidence: 99%